Azulene-based fluorescent chemosensor for adenosine diphosphate - López-Alled, Carlos M.; Park, Sang Jun; Lee, Dong Joon; Murfin, Lloyd C.; Kociok-Köhn, Gabriele; Hann, Jodie L.; Wenk, Jannis; James, Tony D.; Kim, Hwan Myung; Lewis, Simon E. (Chemical Communications, 2021)
AzuFluor® 435-DPA-Zn, an azulene fluorophore bearing two zinc(ii)-dipicolylamine receptor motifs, exhibits fluorescence enhancement in the presence of adenosine diphosphate. Selectivity for ADP over ATP, AMP and PPi results from appropriate positioning of the receptor motifs, since an isomeric sensor cannot discriminate between ADP and ATP.
Keywords: Adenosine diphosphate; Azulenes; Fluorescence enhancement; Fluorescent chemosensors; Adenosine Diphosphate; Azulenes; Fluorescent Dyes; Humans; Molecular Structure; Spectrometry, Fluorescence